Strategi Bisnis Perusahaan Perdagangan di Indonesia: Studi Kasus Pada PT Robotaqua Indonesia - Ambodo, Priyo Kus; Hermawan, Aji; Kirbrandoko; Rahmana, Adhitya (School of Business, Bogor Agricultural University (SB-IPB), 2022)
Trading companies concentrate heavily on profiting from the way the company operates. PT Robotaqua Indonesia is one of the air purifier traders in Indonesia. Since the last two years, business performance has decreased. The purpose of this research is to evaluate the strengths, weaknesses, opportunities, and threats that exist in the business environment of PT Robotaqua Indonesia, to formulate a business strategy that can be carried out by PT Robotaqua Indonesia, to determine recommendation of strategic priorities based on key criteria made by the company. The research was conducted descriptively with the SWOT analysis method and AHP analysis. The results showed 11 alternative strategies based on the condition of the relationship between strengths, weaknesses, opportunities, and threats. As a strategic priority that must be carried out by the company, there are 5 strategies which include increasing the efficiency and effectiveness of inventory management, continuously updating import licensing, increasing sales incentives, developing market segments, and improving after-sales service. Keywords: SWOT Analysis, competitiveness, trading companies, business strategy, AHP